AGE FEATURES OF PHYSICAL DEVELOPMENT PARAMETERS AND COMPONENT COMPOSITION OF THE BODY OF YOUNG URBAN ATHLETES - Boltobaev S.A; Kostikova O.V (Scholar Express Journals, 2022)
The article is devoted to the study of age-related features of the parameters of physical development and the component composition of the body of young urban athletes. It is shown that various types of sports specializations have a significant impact on the parameters of physical development and body composition of urban youths.
Keywords: sports anthropology; anthropometry; body composition; bioimpedance analysis